Pineapple Waste Biorefinery: An Integrated System for Production of Biogas and Marketable Products in South Africa - Reckson Kamusoko; Patrick Mukumba (Biomass, 2025)
Pineapple (Ananas comosus) is one of the most economically important fruit cultivars in South Africa. The fruit is locally consumed, processed into various industrial products or exported to foreign markets. Approximately 115,106 metric tons of pineapple fruit are harvested in South Africa. The pineapple value chain generates significant amounts of waste, in the form of pomace, peel, crown, stem, core and base. If not properly treated, pineapple waste (PAW) could have a profound detrimental impact on the environment. This calls for advanced technological platforms to transform PAW into useful bio-based products. A biorefinery is a potent strategy to convert PAW into multiple food and non-food products while effectively disposing of the waste. The objective of this review is to explore possible pathways for the valorization of PAW into energy and material products in a biorefinery. The paper looks at 10 products including biogas, biohythane, bioethanol, biobutanol, biohydrogen, pyrolytic products, single-cell proteins, animal feed, vermicompost and bioactive compounds. Several platforms (i.e., biochemical, chemical, physical and thermochemical) are available to convert PAW into valuable goods. Amongst them, the biochemical route appears to be the most favorable option for the valorization of PAW. Anaerobic digestion and fermentation are well-established biochemical technologies for PAW valorization. These methods are simple, low-cost, eco-friendly and sustainable. The focal point of emerging research is the enhanced efficacy of biorefinery platforms. The commercialization of PAW biorefining is a potential gamechanger that could revitalize the entire South African economy.